APPLICATION OF REMOTE SENSING, GIS AND DIGITAL SHORELINE ANALYSIS SYSTEM (DSAS) TO ASSESS THE CHANGES OF THE RED RIVER BANK IN THE AREA FROM SON TAY TO GIA LAM (HANOI) - Nhan, Nguyen Thị; Tung, Nguyen Xuan; Anh, Bui Thi Bao; Thanh, Nguyen Xuan (Vietnam Journal of Marine Science and Technology, 2018)
In recent years, some geological hazards relating to the change of channel such as accretion, erosion and landslide of river bank on the Red River bank have occurred more frequently. In this paper, the trend and rate of the change of the Red River bank in the area from Son Tay to Gia Lam (Hanoi) were shown by using remote sensing images of the period 2007–2016, geographic information system (GIS) and Digital shoreline analysis system. The results indicate that bank erosion mainly occurred along the both sides of the Red River bank with the average erosion rate ranging from 1.5 m/yr to 3m/yr. The strongest erosion was along the left river bank in Me Linh commune, Dong Anh district. In Son Tay commune, Phuc Tho district, Vinh Phuc province, some signals of erosion process were also recorded. The accretion process had been occurring in the middle part of the river slowly with the accretion rate of 0.8–1.4 m/yr. In the result, accretion zones were formed and they were aggregated into alluvial flats. In the future, the Red river bank will continue to be changed, erosion and landslide of the channel would be considered as the major hazards in this area.